Assessment of tractor hiring services in Lagos State (2001)
Various agricultural mechanization techniques have been introduced to aid crop production. One of such is intensive use of tractors. Expensive capital and maintenance costs have limited the private ownership of tractors by Nigerian farmers. To promote the use and availability of tractors for farmers, tractor-hiring units were established. Tractor hiring units rent out tractors and other farm implements to farmers at affordable prices. Contrary to expectation, the aim of the program had been defeated due to technical laxity, poor management and the current economic situation of the country. Recognizing the necessity of tractor hiring units, efforts are made on ways of improving performances. Good organization and proper management are needed for effective operation.